European Integration - A Downward Bias in Employment Policies? - Torben Andersen (Center for Economic Studies and ifo Institute (CESifo), 2001)
Even when labour mobility is low, international integration affectslabour markets by making jobs more mobile. This runs via product market integration, which is an essential element of European integration. Increasing job mobility aects the possibilities single countries perceive in pursuing employment policies. In a setting where trade is driven by comparative advantages, and thus wagecompetitiveness plays an important role for employment, it is shown that there is a tendency that a bias arises in employmentpolicies. Policies expanding private employment tend to be used too little, while policies harming private employment tend to be used too much. These effects are stronger the more integratedproduct markets are.
Keywords: F10; F42; J23; J30; 330; spill-overs; coordination; employment.